Byzantine Rome. - LABATT, ANNIE MONTGOMERY (Book collections on Project MUSE., 2022)
Why does medieval Rome look so, for lack of a better word, Byzantine? Why do its monuments speak an aesthetic of the medieval East? And just how do we quantify that Byzantine aesthetic or even the word "Byzantine"?00This book seeks to consider the ways in which the artistic styles and iconographies generally associated with the eastern medieval tradition had a life in the West and, in many cases, were just as western as they were eastern. Rome?s medieval monuments are a fundamental part of the history of the East, a history that says more about a cross- cultural exchange and interconnected "Romes" than difference and separation.00Each chapter follows the political and theological relationships between the East and the West chronologically, exploring the socio-political exchanges as they manifest in the visual language of the monuments that defined the medieval landscape of Rome.